2015
DOI: 10.1017/s1742758415000211
|View full text |Cite
|
Sign up to set email alerts
|

Screening of tropical isolates of Metarhizium anisopliae (Hypocreales: Clavicipitaceae) for virulence to the sweet potato weevil, Cylas formicarius (Coleoptera: Brentidae)

Abstract: The sweet potato weevil (SPW), Cylas formicarius, is a serious pest of sweet potato in Australia and Papua New Guinea. Ten strains of Metarhizium sp. isolated from Australian soil samples were evaluated for their growth characteristics and screened for virulence to adult SPW under laboratory conditions. All isolates except QD62 (48.6%) had moderate to high germination (66 -97%), and all took 2 to 4 days to sporulate at 25 8C. The optimal temperature for radial growth for the majority of isolates was 30 8C, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Generally, the present study recognized superior germination percentage (99.67%) rated by isolate AAUKB-11 whereas the radial growth rate (3.43 mm day À1 ) and sporulation (4.60 Â 10 8 sporse/ml) attained with isolate AAUMFB-77. In entomopathogenic fungi, fast conidia germination, radial growth (Dotaona et al, 2015), and high sporulation rates (Mar et al, 2012) are pathogenicity determinates that positively correlated with fungal virulence. Therefore, screening of entomopathogenic fungi by germination, radial growth, and sporulation parameters could be paramount important to determining high virulent isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the present study recognized superior germination percentage (99.67%) rated by isolate AAUKB-11 whereas the radial growth rate (3.43 mm day À1 ) and sporulation (4.60 Â 10 8 sporse/ml) attained with isolate AAUMFB-77. In entomopathogenic fungi, fast conidia germination, radial growth (Dotaona et al, 2015), and high sporulation rates (Mar et al, 2012) are pathogenicity determinates that positively correlated with fungal virulence. Therefore, screening of entomopathogenic fungi by germination, radial growth, and sporulation parameters could be paramount important to determining high virulent isolates.…”
Section: Discussionmentioning
confidence: 99%
“…used against different hosts (e.g. Brunner-Mendoza et al, 2017;Dotaona et al, 2015;Oreste et al, 2012;Resquín-Romero et al, 2020), and in our study, such variation was also detected when fungal treatments were applied through the spray tower, and for the bait technique. Ondiaka et al (2008) reported intraspecies variability for M. anisopliae and Beauveria bassiana tested against adults of the sweet potato weevil Cylas puncticollis (concentration: 10 7 conidia mL -1 ), and stated that strain selection is needed for biological control.…”
Section: Discussionsupporting
confidence: 74%
“…Standard inoculation procedures were employed for both the adult and larval assays to ensure that consistent spore loads were delivered to each insect and results were thus comparable to other EPF bioassays. The immersion treatment protocol used on adult Carpophilus beetles in this study gave rise to an average mortality rate that was considerably lower compared to similar EPF assays conducted on other adult Coleoptera: for example nine isolates of Metarhizium anisopliae on sweet potato weevil using the same inoculation method, carrier, time and dose-rate, had 100% mortality after 10 days in six of the nine isolates [28]. Similarly, mortality rates between 97.5%-100% for emerald ash borer adults treated with three B. bassiana and two M. anisopliae isolates under the same application regime, incubated for six days [29].…”
Section: Discussionmentioning
confidence: 71%